Pengaruh Kemiskinan, Pertumbuhan Ekonomi, dan Indeks Pembangunan Manusia Terhadap Ketimpangan Pendapatan - Ardiani, Dewi Rilla; Prabowo, Prayudi Setiawan (Universitas Negeri Surabaya, 2024)
Income inequality is the highest source of social inequality in Indonesia. This study aims to determine whether income inequality is influenced by poverty, economic growth, and human development index with a case study of 34 provinces in Indonesia in 2018-2022. This research uses a quantitative approach. The type of data used in this study is secondary data obtained from the publication site of the Central Statistics Agency (BPS) in the form of data on the percentage of the number of poor people, GRDP, HDI, and Gini ratio. The data analysis technique used is panel data regression using Eviews-12 with the best model chosen is the Fixed Effect Model (FEM). The results of this study show that partially the poverty variable has a positive effect, the economic growth variable has no effect, and the human development index variable has a negative effect on provincial income inequality in Indonesia. Simultaneously, poverty, economic growth and human development index have a positive and significant effect on provincial income inequality in Indonesia.